First downhole sampling of a natural hydrogen reservoir in Colombia - Patiño, Cesar; Strąpoć, Dariusz; Torres, Oscar; Mullins, Oliver; Bustos, Ulises; Bermudez, Oscar; López, Albeiro; Trujillo, Maria; Morales, Hans (Frontiers in Energy Research, 2024)
We co-authors believe that our manuscript entitled "First downhole sampling of a natural H2 reservoir in Colombia" is suitable to the Frontiers Research Topic "Understanding Natural H2 Systems-their Exploration and Stimulation", because: -It describes one of the world's first and pioneering natural H2 exploration approach leading through all the stages (i.e., seismic interpretation, seep surveys, drilling, logging, eventually leading to a representative downhole sampling. -Each of these steps is described in detail and explains complexity of the workflow of exploration of this new resource. -Finally, this is a joint industry effort between an energy company and a service company, benefiting from practical and field-data based publication, that could serve as a showcase for H2 exploration worldwide, especially in similar geologic scenarios.